Mapping the Dynamics of the Glucocorticoid Receptor within the Nuclear Landscape - Stortz, Martin Dario (2017)
The distribution of the transcription machinery among different sub-nuclear domains raises the question on how the architecture of the nucleus modulates the transcriptional response. Here, we used fluorescence fluctuation analyses to quantitatively explore the organization of the glucocorticoid receptor (GR) in the interphase nucleus of living cells. We found that this ligand-activated transcription factor diffuses within the nucleus and dynamically interacts with bodies enriched in the coregulator NCoA-2, DNA-dependent foci and chromatin targets. The distribution of the receptor among the nuclear compartments depends on NCoA-2 and the conformation of the receptor as assessed with synthetic ligands and GR mutants with impaired transcriptional abilities. Our results suggest that the partition of the receptor in different nuclear reservoirs ultimately regulates the concentration of receptor available for the interaction with specific targets, and thus has an impact on transcription regulation.